The impact of OSHA recordkeeping regulation changes on occupational injury and illness trends in the US: a time-series analysis. Issue 7 (15th February 2007) - Friedman, Lee S; Forst, Linda
Abstract : Objectives: The Survey of Occupational Injuries and Illnesses (SOII), based on Occupational Safety and Health Administration (OSHA) logs, indicates that the number of occupational injuries and illnesses in the US has steadily declined by 35.8% between 1992–2003. However, major changes to the OSHA recordkeeping standard occurred in 1995 and 2001. The authors assessed the relation between changes in OSHA recordkeeping regulations and the trend in occupational injuries and illnesses. Methods: SOII data available from the Bureau of Labor Statistics for years 1992–2003 were collected. The authors assessed time series data using join-point regression models. Results: Before the first major recordkeeping change in 1995, injuries and illnesses declined annually by 0.5%. In the period 1995–2000 the slope declined by 3.1% annually (95% CI −3.7% to −2.5%), followed by another more precipitous decline occurring in 2001–2003 (−8.3%; 95% CI −10.0% to −6.6%). When stratifying the data, the authors continued to observe significant changes occurring in 1995 and 2001. Conclusions: The substantial declines in the number of injuries and illnesses correspond directly with changes in OSHA recordkeeping rules. Changes in employment, productivity, OSHA enforcement activity and sampling error do not explain the large decline. Based on the baseline slope (join-point regression analysis, 1992–4), the authors expected a decline of 407 964 injuries and illnesses during the period of follow-up if no intervention occurred; they actually observed a decline of 2.4 million injuries and illnesses of which 2 million or 83% of the decline can be attributed to the change in the OSHA recordkeeping rules.